2020
DOI: 10.9734/ijpss/2020/v32i530280
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pomological and Chemical Properties of Autochthonous Pear Varieties with Standard Pear Varieties

Abstract: Indigenous fruit varieties are the wealth and natural resource of every country. Their importance is reflected, in addition to economic and biological, through the growing consumer interest in consuming fruits produced without the use of chemicals. Proper and accurate identification and preservation of valuable assortment has resulted in studies of the physicochemical and pomological properties of the fruits of ten pear varieties and their comparison with standard varieties. The usable value of pear fruits is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…This statement is supported by Ref. [40] and is a positive issue for the dissemination of this innovative in situ preservation of pear biodiversity. In addition, compared to other rootstocks, wild pear ones are highly resistant to both biotic and abiotic stresses contributing to the build-up of a secondary metabolite sink in the fruit.…”
Section: Discussionmentioning
confidence: 57%
“…This statement is supported by Ref. [40] and is a positive issue for the dissemination of this innovative in situ preservation of pear biodiversity. In addition, compared to other rootstocks, wild pear ones are highly resistant to both biotic and abiotic stresses contributing to the build-up of a secondary metabolite sink in the fruit.…”
Section: Discussionmentioning
confidence: 57%
“…Pear (Pyrus spp.) has a special place in the agricultural production of Bosnia and Herzegovina, as it can be grown in a wide range of climatic and soil conditions, has a prolonged maturation from early summer to late autumn, and produces fruit with good nutritional value, which is classified as nutrient-dense [1]. Pear fruits are an excellent source of dietary fiber; amino acids; minerals such as sodium, potassium, calcium, magnesium, and iron; and vitamins, which are very important health-beneficial biocomponents [2].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent studies have reported a significantly higher concentration of PC among traditional cultivars compared to commercial ones [6,13]. Traditional pear cultivars from Bosnia and Herzegovina possess several advantageous traits [14,15], including important morphological, pomological, eco-physiological, and nutritional characteristics of the fruit [1,16,17]. Local pear genotypes are highly appreciated by consumers due to their use in processing high-value fruit products (juices, nectars, dried fruit, purees, 'pekmez', and jams).…”
Section: Introductionmentioning
confidence: 99%